A Regularity Criterion for the Magneto-Micropolar Fluid Equations in B˙∞,∞−1 - Zhihao Tang; Gang Wang; Haiwa Guan (Discrete Dynamics in Nature and Society)
The paper is dedicated to study of the Cauchy problem for the magneto-micropolar fluid equations in three-dimensional spaces. A new logarithmically improved regularity criterion for the magneto-micropolar fluid equations is established in terms of the pressure in the homogeneous Besov space B˙∞,∞−1.